Umur dan Perubahan Kondisi Fisiologis Terhadap Kemandirian Lansia - Dianita Sugiyo (Universitas Muhammadiyah Yogyakarta, 2014)
Background. This study aims to determine the relationship between age and changes in physiological conditions of the elderly in Posyandu Ngudirahayu independence Tlogo Tamantirta Kasihan Bantul. Methodology. The study was observational research using cross sectional and correlation analyzed. The sample size is 44 elderly and the sampling technique used was purposive sampling. Data collection instrument Visual Analogue Scale (VAS), questionnaires HHIE-S and Katz index. Test this hypothesis using Spearmans Rho correlation test. The results showed respondents of 60-74 years old is 61.4% and 75-90 years as much as 38.6%, The results of Spearman's Rho correlation was the relationship between the age and level of independence of the elderly signifi cance value (p) = 0.001 (p 0.05 ) and the value of the correlation coeffi cient (r) = 0.479. Respondents with mild joint pain (25.0%), moderate joint pain (52.3%) and 22.7% of severe pain the results of Spearman's Rho correlation was the relationship between the joint pain with a level of independence elderly signifi cance value (p) = 0.019 (p 0.05) and the value of the correlation coeffi cient (r) = 0.351. Respondents with mild-moderate of auditory function as much as 45.5%, signifi cantly much as 15.9%, and 38.6% as much as normal, the results of Spearman's Rho correlation was the relationship between auditory function with a degree of independence of elderly signifi cance value (p) =0.080 (p 0.05) and the value of the correlation coeffi cient (r) = 0.267. Level of independence of the respondents classifi ed as fully independent (type A) 54.5%, partially independent (type B, C, D, E, F) of 27.3%, and dependence (type G and others) as much as 18.2%. Conclusion. A signifi cant relationship between age and joint pain to the elderly independence, but for variable auditory function was not related to the independence of the elderly. Keywords: Elderly, Age, joint pain, auditory function, level of independence